Newly discovered roles of triosephosphate isomerase including functions within the nucleus - Tracey D. Myers; Michael J. Palladino (BMC, 2023)
Abstract Triosephosphate isomerase (TPI) is best known as a glycolytic enzyme that interconverts the 3-carbon sugars dihydroxyacetone phosphate (DHAP) and glyceraldehyde-3-phosphate (G3P). TPI is an essential enzyme that is required for the catabolism of DHAP and a net yield of ATP from anaerobic glucose metabolism. Loss of TPI function results in the recessive disease TPI Deficiency (TPI Df). Recently, numerous lines of evidence suggest the TPI protein has other functions beyond glycolysis, a phenomenon known as moonlighting or gene sharing. Here we review the numerous functions ascribed to TPI, including recent findings of a nuclear role of TPI implicated in cancer pathogenesis and chemotherapy resistance.